Quadratic expressions have the general form \[ax^2+bx+c\] where \(a\), \(b\) and \(c\) are real numbers and \(a\neq 0\). Quadratics frequently arise in mathematics, science and engineering. This module explains how to factorise a quadratic into two linear factors. For example \[x^2+5x+6 = \left(x+2\right)\left(x+3\right).\]
The general form of a quadratic expression is: \(ax^{2}+bx+c\), \(a\neq0\), where \(a\), \(b\) and \(c\) are real constants and \(x\) is the variable.
We will initially work with expressions that have \(a=1\) so the expression becomes \(x^{2}+bx+c\).
Expansion
To expand an expression of the form \((a+b)(c+d)\), multiply each term in the first bracket by each term in the second bracket.
\(x^{2}+5x+6\) is expressed as the product of two factors, \((x+2)\) and \((x+3).\) That is \[\begin{align*} x^{2}+5x+6 & =\left(x+2\right)\left(x+3\right). \end{align*}\]
Note that:
Multiplying the first term in each bracket gives the term \(x^{2}\) in the expression as above.
Multiplying the last term in each bracket gives the constant term, \(+6\) in the expression.
The coefficient of the \(x\) term is the sum of the last term in each bracket \((+2+3=+5)\).
The basic rule is:
To factorise \(x^{2}+bx+c\), find two numbers \(m\) and \(n\) such that \[\begin{align*} x^{2}+bx+c & =\left(x+m\right)\left(x+n\right) \end{align*}\] where \(m\times n=c\) and \(m+n=b.\)
Note that order of the factors does not matter. That is \[\begin{align*} x^{2}+bx+c & =\left(x+m\right)\left(x+n\right)\\ & =\left(x+n\right)\left(x+m\right). \end{align*}\]
Example 1
Factorise \(x^{2}+9x+14.\)
Solution
We want to write \[\begin{align*} x^{2}+9x+14 & =\left(x+m\right)\left(x+n\right) \end{align*}\] where according to the rule above, \[\begin{align*} m\times n & =14\ \text{and }\\ m+n & =9. \end{align*}\]
The factors of \(14\) are
\[\begin{align*} 1.\ m & =1 & 2.\ m & =-1 & 3.\ m & =2 & 4.\ m & =-2\\ n & =14 & n & =-14 & n & =7 & n & =-7. \end{align*}\] Of these, only the factors in \(3\) satisfy the requirement that \(m+n=9\). So \[\begin{align*} x^{2}+9x+14 & =\left(x+2\right)\left(x+7\right). \end{align*}\]
Example 2
Factorise \(y^{2}-7y+12\).
Solution
We want to write \[\begin{align*} y^{2}-7x+12 & =\left(y+m\right)\left(y+n\right) \end{align*}\] where according to the rule above, \[\begin{align*} m\times n & =12\ \text{and }\\ m+n & =-7. \end{align*}\]
The factors of \(12\) are
\[\begin{align*} 1.\ m & =3 & 2.\ m & =-3 & 3.\ m & =2 & 4.\ m & =-2 & 5.\ m & =12 & 6.\ m & =-12\\ n & =4 & n & =-4 & n & =6 & n & =-6 & n & =1 & n & =-1. \end{align*}\] Of these, only the factors in \(2\) satisfy the requirement that \(m+n=-7\). So \[\begin{align*} y^{2}-7x+12 & =\left(y-3\right)\left(y-4\right). \end{align*}\]
Example 3
Factorise \(p^{2}-5p-14\).
Solution
We want to write \[\begin{align*} p^{2}-5p-14 & =\left(p+m\right)\left(p+n\right) \end{align*}\] where according to the rule above, \[\begin{align*} m\times n & =14\ \text{and }\\ m+n & =-5. \end{align*}\]
The factors of \(-14\) are
\[\begin{align*} 1.\ m & =1 & 2.\ m & =-1 & 3.\ m & =-2 & 4.\ m & =2\\ n & =-14 & n & =14 & n & =7 & n & =-7. \end{align*}\] Of these, only the factors in \(4\) satisfy the requirement that \(m+n=-5\). So \[\begin{align*} p^{2}-5x-14 & =\left(p+2\right)\left(p-7\right). \end{align*}\]
Example 4
Factorise \(a^{2}+6a-7\).
Solution
We want to write \[\begin{align*} a^{2}+6a-7 & =\left(a+m\right)\left(a+n\right) \end{align*}\] where according to the rule above, \[\begin{align*} m\times n & =-7\ \text{and }\\ m+n & =6. \end{align*}\]
The factors of \(-7\) are
\[\begin{align*} 1.\ m & =1 & 2.\ m & =-1\\ n & =-7 & n & =7 \end{align*}\]
Of these, only the factors in \(2\) satisfy the requirement that \(m+n=6\). So \[\begin{align*} a^{2}+6a-7 & =\left(a-1\right)\left(a+7\right). \end{align*}\]
Example 5 (no real factors)
Factorise \(a^{2}+3a+6\).
Solution
We want to write \[\begin{align*} a^{2}+3a+6 & =\left(a+m\right)\left(a+n\right) \end{align*}\] where according to the rule above, \[\begin{align*} m\times n & =6\ \text{and }\\ m+n & =3. \end{align*}\]
The factors of \(6\) are \[\begin{align*} 1.\ m & =1 & 2.\ m & =-1 & 3.\ m & =-2 & 4.\ m & =2\\ n & =6 & n & =-6 & n & =-3 & n & =3. \end{align*}\]
None of these factors satisfy the requirement that \(m+n=3\). So it is not possible to factorise the expression \[\begin{align*} a^{2}+3a+6 & . \end{align*}\] In this case we say there are no real factors.1 Geometrically this means that the graph of \(y=a^{2}+3a+6\) does not touch or intersect the \(a-\text{axis$.$ }\) There are complex factors but these are not dealt with in this module. It is important to understand when this occurs and is discussed in a later section.
Factorisation when \(a\neq1\)
In this section we deal with factorisation of expressions of the form \[\begin{align*} ax^{2}+bx+c \end{align*}\] where \(a\neq1.\)
Expressions of the type \(ax^{2}+bx+c\) can be factorised using a technique similar to that used for expressions of the type \(x^{2}+bx+c.\)
In this case the coefficient of \(x\), in at least one bracket, will not equal 1.
multiplying the first term in each bracket gives the \(x^{2}\) term. In this case \(6x^{2}.\)
multiplying the last term in each bracket gives the constant term, in this case \(2.\)
the coefficient of the \(x-\)term is the sum of the \(x\) terms in the expansion. In this case \(3x+4x=7x.\)
We can use these ideas to factorise expressions like \(ax^{2}+bx+c\).
Example 6
Factorise \(2x^{2}+7x+6\).
Solution
The only factors of the coefficient of the \(x^{2}\) term are \(2\) and 1. So we are looking for a factorisation like \[\begin{align*} 2x^{2}+7x+6 & =\left(2x+m\right)\left(x+n\right)\text{}\\ & =2x^{2}+2nx+mx+nm\\ & =2x^{2}+\left(2n+m\right)x+nm \end{align*}\] where \(mn=6\) and \(2n+m=7.\) We have the following possibilities:2 Note that negative factors like \(m=-6,\,n=-1\) and \(m=-1,\,n=-6\) don’t need to be considered as they don’t satisfy condition \(2n+m=7\).
\(m=3,\ \:n=2\)
\(m=2,\ \ n=3\)
\(m=6,\ \:n=1\)
Of these possibilities, the only one that satisfies \(2n+m=7\) is number \(1.\) That is \(m=2\text{ and }n=2\), so \[\begin{align*} 2x^{2}+7x+6 & =\left(2x+3\right)\left(x+2\right). \end{align*}\]
Example 7
Factorise \(2x^{2}-10x+12.\)
Solution
At first this looks like a case where \(a=2\) but a factor of \(2\) can be taken out to get: 3 You should always check if there is a number that divides into all terms of the quadratic. \[\begin{align*} 2x^{2}-10x+12 & =2\left(x^{2}-5x+6\right) \end{align*}\] Now we can use the methods in Examples \(1-4\) above to get
\[\begin{align*} 2x^{2}-10x+12 & =2\left(x+m\right)\left(x+n\right) \end{align*}\] where \(mn=6\) and \(m+n=-5.\) This implies \(m=-2\) and \(n=-3\) and so: \[\begin{align*} 2x^{2}-10x+12 & =2\left(x^{2}-5x+6\right)\\ & =2\left(x-2\right)\left(x-3\right). \end{align*}\]
Example 8
Factorise \(6x^{2}+13x-8\).
Solution
In this case there are no numbers that divide into each term as we had in Example 7 above. The coefficient of the \(x^{2}\) term is \(6\) which has factors \[\begin{align*} 6 & =6\times1\\ & =2\times3. \end{align*}\] So we are looking for a factorisation such as: \[\begin{align*} 6x^{2}+13x-8 & =\left(6x+m\right)\left(x+n\right)\\ & =6x^{2}+6xn+mx-8\\ & =6x^{2}+\left(6n+m\right)x-8 & \left(8.1\right) \end{align*}\] or \[\begin{align*} 6x^{2}+13x-8 & =\left(3x+m\right)\left(2x+n\right)\\ & =6x^{2}+3xn+2mx-8\\ & =6x^{2}+\left(3n+2m\right)x-8 & \left(8.2\right) \end{align*}\] In both cases, \(mn=-8.\) So we have the possibilities \[\begin{align*} m & =-8 & n & =1\\ m & =8 & n & =-1\\ m & =4 & n & =-2\\ m & =-4 & n & =2. \end{align*}\]
For eqn \(\left(8.1\right)\) we know that \(6n+m=13\). This is not satisfied by any of the \(m\) and \(n\) values above.
For eqn \(\left(8.2\right)\) we know that \(3n+2m=13\). This is satisfied by \(m=8\) and \(n=-1\) and so \[\begin{align*} 6x^{2}+13x-8 & =\left(3x+8\right)\left(2x-1\right). \end{align*}\]
Example 9
Factorise \(4x^{2}+4x+1\)
Solution
In this case there are no numbers that divide into each term as we had in Example 7 above. The coefficient of the \(x^{2}\) term is \(4\) which has factors \[\begin{align*} 4 & =4\times1\\ & =2\times2. \end{align*}\]
So we are looking for a factorisation such as: \[\begin{align*} 4x^{2}+4x+1 & =\left(4x+m\right)\left(x+n\right)\\ & =4x^{2}+4xn+mx+mn\\ & =4x^{2}+\left(4n+m\right)x+1 & \left(9.1\right) \end{align*}\] or \[\begin{align*} 4x^{2}+4x+1 & =\left(2x+m\right)\left(2x+n\right)\\ & =4x^{2}+2xn+2mx+mn\\ & =4x^{2}+\left(2n+2m\right)x+1 & \left(9.2\right) \end{align*}\] where \(mn=1\). That means \[\begin{align*} m & =1 & n= & 1 & \left(9.3\right)\\ m & =-1 & n= & -1. & \left(9.4\right) \end{align*}\] Suppose eqn \(\left(9.1\right)\) is correct then \(\left(4n+m\right)=4.\) But this is not possible with the choices for \(m\) and \(n\) in \(\left(9.3\right)\) and \(\left(9.4\right)\). Hence the factorisation must be as in eqn \(\left(9.2\right)\) with \(2n+2m=4.\) The latter is achieved with \(\left(9.3\right)\) and so \[\begin{align*} 4x^{2}+4x+1 & =\left(2x+1\right)\left(2x+1\right). \end{align*}\]
The approach given in examples 6-9 is okay provided there are not too many factors for \(a\) and \(c\). If the number of factors is excessive, we can employ other methods.
When can you get real linear factors for a quadratic?
In Example 5 above we found that we could not get real linear factors for \[\begin{align*} a^{2}+3a+6 & . \end{align*}\]
This raises the question of when real solutions to general quadratics may be found. The most general quadratic has the form 4 Note that the graph of \[\begin{align*} y & =ax^{2}+bx+c \end{align*}\] is a parabola. \[\begin{align*} ax^{2}+bx+c & . \end{align*}\]
To determine if there are real linear factors, we introduce the discriminant.
The discriminant
The discriminant denoted \(\Delta,\) for the general quadratic \[\begin{align*} ax^{2}+bx+c \end{align*}\] is \[\begin{align*} \Delta & =b^{2}-4ac. \end{align*}\]
If \[\begin{align*} \Delta & =\begin{cases} 0\text{ there is one repeated linear factor}\\ >0\text{ there are two distinct linear factors}\\ <0\text{ there are no real linear factors.} \end{cases} \end{align*}\] The discriminant tells us how many real roots there are to the equation 5 Geometrically, the discriminant tells us how many times the graph of \[\begin{align*} y & =ax^{2}+bx+c \end{align*}\] intersects the \(x-\)axis. If \(\Delta=0\), the graph just touches the \(x-\)axis at one point. If \(\Delta>0,\) the graph intersects the \(x-\)axis at two points. If \(\Delta<0,\) the graph does not intersect the \(x-\)axis.\[\begin{align*} ax^{2}+bx+c=0 & . \end{align*}\]
Example 10
Factorise (if possible) \(x^{2}+6x+12\)
Solution
In this case: \(a=1\) , \(b=+6\) , \(c=+12\) therefore
\[\begin{align*} \Delta & =\left(b^{2}-4ac\right)\\ & =36-4(1)(12)\\ & =36-48\\ & =-12\\ & <0. \end{align*}\] The discriminant is negative therefore \(x^{2}+6x+12\) has no real factors.
Exercise 1
Factorise the following expressions (if possible):